Everyday guides made easy Microsoft Windows basics - Stables, James (Flame Tree Publishing, 2015)
Microsoft Windows Basics is the essential guide for all those who want to get to grips with the basics of Microsoft Windows. Written in a clear and accessible way it starts by covering everything from the basics of the traditional features such as security and using the internet to organising folders and files. In addition you will learn how to make the most of the new features of Windows 8 such as accessing and downloading apps from the Windows Store and using the operating system on touchscreen.